2020
DOI: 10.1016/j.geoderma.2020.114481
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water repellency on the short-term release of CO2 upon soil wetting

Abstract: The spike in carbon dioxide (CO2) observed after rewetting of dry soils, known as the 'Birch effect', can contribute substantially to total soil carbon (C) emissions, however, the exact mechanisms and timings underlying this sudden CO2 release remain unclear. The amount of applied water and duration of the previous dry period are considered the main factors affecting the magnitude of the CO2 peak, but the preceding change in soil wettability, triggered by low soil water content, could also be an important cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The moisture‐response function in conventional models affects the decomposition rates of different soil C pools and their response to environmental changes (Moyano et al., 2013), while in microbial models, the moisture‐response function is generally considered to modify the function of Michaelis‐Menten kinetics when microbial mechanisms are embedded in models (Abramoff et al., 2018; Wieder et al., 2013). Other factors can also affect the mechanistic relationship between the R H and soil moisture, such as soil properties in pore‐scale models (Moyano et al., 2012, 2013), microbial dormancy (Salazar et al., 2018), and soil water transfer processes (Manzoni et al., 2014, 2016; Sánchez‐García, Doerr, et al., 2020; Sánchez‐García, Oliveira, et al., 2020). Yan et al.…”
Section: Discussionmentioning
confidence: 99%
“…The moisture‐response function in conventional models affects the decomposition rates of different soil C pools and their response to environmental changes (Moyano et al., 2013), while in microbial models, the moisture‐response function is generally considered to modify the function of Michaelis‐Menten kinetics when microbial mechanisms are embedded in models (Abramoff et al., 2018; Wieder et al., 2013). Other factors can also affect the mechanistic relationship between the R H and soil moisture, such as soil properties in pore‐scale models (Moyano et al., 2012, 2013), microbial dormancy (Salazar et al., 2018), and soil water transfer processes (Manzoni et al., 2014, 2016; Sánchez‐García, Doerr, et al., 2020; Sánchez‐García, Oliveira, et al., 2020). Yan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, deterioration of the water regime, which creates an anaerobic environment in the soil, influences the direction of organic matter transformation, causing a significant increase in soil hydrophobicity (Mielnik et al, 2021). Sánchez‐García, Doerr, and Urbanek (2020); Sánchez‐García, Oliveira, et al (2020) and Urbanek and Doerr (2017) showed that soil hydrophobicity can become a key factor affecting the release of CO 2 , especially during rainfall events. However, the interactions between water and hydrophobic particles derived from organic soil residues, which depend on the variability of environmental factors, such as temperature and soil biological activity, remain largely unrecognised (Mao et al, 2019; Seaton et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The specific objectives and a more detailed structure of this thesis are outlined at the end of Chapter 1. Chapters 2 and 3 are versions of peerreviewed publications (Sánchez-García et al, 2020a; and the material from Chapter 4 forms a third publication currently under second revision in a peer-reviewed journal (Sánchez-García et al, In submission). Chapters 2, 3 and 4 have been reformatted to incorporate the published articles and to ensure consistency throughout the thesis.…”
Section: Introduction and Thesis Outlinementioning
confidence: 99%